2008
DOI: 10.1080/08873260701828870
|View full text |Cite
|
Sign up to set email alerts
|

On the measurement of meaning: Logotherapy's empirical contributions to humanistic psychology.

Abstract: Meaningful living is a central focus of several humanistic theories and therapies. Measurement of life meaning meets many obstacles, including pragmatic concerns, such as measuring subjective experiences, and theoretical objections often offered by humanistic psychologists. The purpose of this article is to summarize empirical efforts related to logotherapy, a humanistic-existential paradigm, to illustrate the utility of assessment within the larger context of humanistic psychology. An overview of five logothe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
82
0
14

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 108 publications
(105 citation statements)
references
References 45 publications
3
82
0
14
Order By: Relevance
“…Decades of research have supported Frankl's main assumptions, showing MIL as an important predictor of physical health (Jim & Andersen, 2007), psychological well-being and quality of life (Fillion et al, 2009;Ho et al, 2010;Melton & Schulenberg, 2008). A lack of meaning, on the other hand, has been associated with higher depression levels (Mascaro & Rosen, 2006), suicidal ideas (Edwards & Holden, 2001), drug addiction (Henrion, 2002), among others.…”
Section: Meaning In Life and Its Relations With Health Aspectsmentioning
confidence: 94%
See 1 more Smart Citation
“…Decades of research have supported Frankl's main assumptions, showing MIL as an important predictor of physical health (Jim & Andersen, 2007), psychological well-being and quality of life (Fillion et al, 2009;Ho et al, 2010;Melton & Schulenberg, 2008). A lack of meaning, on the other hand, has been associated with higher depression levels (Mascaro & Rosen, 2006), suicidal ideas (Edwards & Holden, 2001), drug addiction (Henrion, 2002), among others.…”
Section: Meaning In Life and Its Relations With Health Aspectsmentioning
confidence: 94%
“…Also, teachers with higher MIL rates may also perceive life more optimistically. As the meaning in life is positively related with constructs like faith, love, happiness, optimism and hope (Ho et al, 2010;Melton & Schulenberg, 2008;) and is considered a fundamental aspect in the resilience process (Schulenberg & Melton, 2010), the presence of this resource seems to optimize teachers' satisfaction with different aspects of their lives.…”
Section: Meaning In Life and Its Relations With Psychological Well-bementioning
confidence: 99%
“…Responses are given on a 7-point Likert-type scale, the poles of which vary according to the question. Melton and Schulenberg (2008) reviewed studies that reported alpha coefficients ranging from 0.86 to 0.97. Alpha reliability in this sample was 0.89.…”
Section: The Purpose In Life Test (Pilt)mentioning
confidence: 99%
“…Unlike all the other measures discussed here, the MED uses a qualitative methodology in which respondents answer, in writing or orally during interviews, two personal questions related to meaning in life. Melton and Schulenberg (2008) report findings from a variety of studies that report that these instruments have reliable internal consistency and validity.…”
Section: Scope Of This Reviewmentioning
confidence: 99%
“…The measure has been used in numerous studies and found to be a valid and reliable instrument (Crumbaugh & Maholick, 1964, 1969Chamberlain & Zika, 1988;Zika & Chamberlain, 1992;Reker, 1977;Melton & Schulenberg, 2008). Researchers using the PIL test have found relatively low senses of life purpose among high school students involved in the use of narcotics (Padelford, 1974), prison inmates (Reker, 1977), apathetic college students (Coffienld, 1981 ), patients with psychopathological syndromes (Gonsalvez & Gon, 1983), drug addicts (Nicholson, et al, 1994), college students with anger issues (Sappington & Kelly, 1995), adolescent children of Bangladeshi divorcees (Rahman, 2004); and college students who engage in isolating verses interpersonal activities (Molasso, 2006).…”
Section: Purpose In Life (P Il) Testmentioning
confidence: 99%